2009
DOI: 10.1007/s15010-008-8124-x
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Profile for Invasive Aspergillosis in Liver Transplant Recipients

Abstract: The rate of IA found in this investigation is within the range reported in published studies. Based on our data, extended antifungal prophylaxis should be given to liver transplant patients with specific risk factors, such as renal insufficiency, requirement for dialysis, CMV infection, or thrombocytopenia. Additional focus should be on the prevention of CMV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 39 publications
4
69
0
Order By: Relevance
“…1,7,9,10 Similarly, our study found that fungal infections occur more often in recipients with a retransplant.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…1,7,9,10 Similarly, our study found that fungal infections occur more often in recipients with a retransplant.…”
Section: Discussionsupporting
confidence: 76%
“…1,2,4,[8][9][10] In some of these reports, age was not found to be a significant factor for developing invasive fungal infections. 1,9,10 In contrast with previous reports, we found significant differences between recipients with and without invasive fungal infections. Liver transplant recipients with an older age at transplant showed a higher incidence of invasive fungal infections compared with patients with a younger age at transplant.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations